SELF MANAGEMENT INTERVENTION INCREASING COMPLIANCE IN PATIENT WITH DM - Siti Nur Kholifah (Universitas Airlangga, 2017)
Introduction: Diabetes mellitus (DM) was a degenerative disease which often found in the community. Diabetes was caused by unhealthy habits, such as overeating, lack of exercise, and stress. The purpose of this study was to identify selfmanagement as one of the interventions that can improve treatment compliance in patients with diabetes. Method: This study was used quasy experiments non randomized pretest-posttest design. Samples were 20 families who lived with type 2 diabetes patient. Variable independent was self management intervention and variable dependent was patient complience. Data were collected by using interview, food recall, and observation on behavioral change. Data then analyzed by using paired t-test with α≤0.05. Results: The results had showed that before intervention only 3 (15 %) respondents who obey diabetes diet, then increase to 19 (95 %) respondents after intervention with p value=0.000. Patient's medication compliance also increased, from 6 (30 % ) respondents before intervention to 20 (100%) respondents after intervention, with p value= 0.000. Patient compliance on exercise also increase from 2 (10%) respondents before intervention, become 19 (95%) respondents after intervention, with p value=0.000. Discussion: Self management intervention could improve patient's knowledge, problem-solving skills, and self-effi cacy. Self management should be done after the patient had understand their disease and realized the importance of self-care. Community health nurses were expected to implement self management as one of nursing intervention, so that patient compliance on their treatment can be increased. Key words: Self management intervention, compliance, patient DM type 2